Crowdfunding: Decisiones de implementación en las industrias creativas de países emergentes (2011)
The participation mechanisms to finance projects from the support of cyberspace communities has generated new opportunities for creative industries to make their initiatives come true. Crowdfunding is an alternative complementary to traditional financing structures and it uses online platforms to establish a relationship between content developers and their audiences. This document describes the decisions made by a creative industry for their implementation from the 'El Cosmonauta' (The Cosmonaut), experience which is a Spanish science fiction film that applies this model. The analysis is based on the compilation of online information (web sites and social network) about this movie and on the film advances follow up in social networks. Although this practice can work for all kinds of projects, its application emphasizes proposals related to movies, video games and Internet based initiatives.